NK cells from tuberculous pleurisy express high ICAM-1 levels and exert stimulatory effect on local T cells - Schierloh, Luis Pablo (2009)
Tuberculous pleurisy, one of the most common manifestations of extrapulmonary tuberculosis, is characterized by a T-cell-mediated hypersensitivity reaction along with a Th1 immune profile. In this study, we investigated functional cross-talk among T and NK cells in human tuberculous pleurisy. We found that endogenously activated pleural fluid-derived NK cells express high ICAM-1 levels and induce T-cell activation ex vivo through ICAM-1. Besides, upon in vitro stimulation with monokines and PAMP, resting peripheral blood NK cells increased ICAM-1 expression leading to cellular activation and Th1 polarization of autologous T cells. Furthermore, these effects were abolished by anti-ICAM-1 Ab. Hence, NK cells may contribute to the adaptive immune response by a direct cell-contact-dependent mechanism in the context of Mycobacterium tuberculosis infection. © 2009 Wiley-VCH Verlag GmbH © Co. KGaA.